New-to-nature CO2-dependent acetyl-CoA assimilation enabled by an engineered B12-dependent acyl-CoA mutase - Helena Schulz-Mirbach; Philipp Wichmann; Ari Satanowski; Helen Meusel; Tong Wu; Maren Nattermann; Simon Burgener; Nicole Paczia; Arren Bar-Even; Tobias J. Erb (Nature Communications)
Abstract Acetyl-CoA is a key metabolic intermediate and the product of various natural and synthetic one-carbon (C1) assimilation pathways. While an efficient conversion of acetyl-CoA into other central metabolites, such as pyruvate, is imperative for high biomass yields, available aerobic pathways typically release previously fixed carbon in the form of CO2. To overcome this loss of carbon, we develop a new-to-nature pathway, the Lcm module, in this study. The Lcm module provides a direct link between acetyl-CoA and pyruvate, is shorter than any other oxygen-tolerant route and notably fixes CO2, instead of releasing it. The Lcm module relies on the new-to-nature activity of a coenzyme B12-dependent mutase for the conversion of 3-hydroxypropionyl-CoA into lactyl-CoA. We demonstrate Lcm activity of the scaffold enzyme 2-hydroxyisobutyryl-CoA mutase from Bacillus massiliosenegalensis, and further improve catalytic efficiency 10-fold by combining in vivo targeted hypermutation and adaptive evolution in an engineered Escherichia coli selection strain. Finally, in a proof-of-principle, we demonstrate the complete Lcm module in vitro. Overall, our work demonstrates a synthetic CO2-incorporating acetyl-CoA assimilation route that expands the metabolic solution space of central carbon metabolism, providing options for synthetic biology and metabolic engineering.